TssA from Burkholderia cenocepacia: expression, purification, crystallization and crystallographic analysis - Owen, Hayley J.; Sun, Ruyue; Ahmad, Asma; Sedelnikova, Svetlana E.; Baker, Patrick J.; Thomas, Mark S.; Rice, David W. (Acta crystallographica. Section F, Structural biology communications, 2018)
TssA is a core component of the type VI secretion system, and phylogenetic analysis of TssA subunits from different species has suggested that these proteins fall into three distinct clades. Whilst representatives of two clades, TssA1 and TssA2, have been the subjects of investigation, no members of the third clade (TssA3) have been studied. Constructs of TssA from Burkholderia cenocepacia, a representative of clade 3, were expressed, purified and subjected to crystallization trials. Data were collected from crystals of constructs of the N‐terminal and C‐terminal domains. Analysis of the data from the crystals of these constructs and preliminary structure determination indicates that the C‐terminal domain forms an assembly of 32 subunits in D16 symmetry, whereas the N‐terminal domain is not involved in subunit assocation. Analysis of the noncrystallographic symmetry of crystals of the C‐terminal domain of Burkholderia cenocepacia TssA indicates a quaternary structure of 32 subunits in D16 symmetry.